2018
DOI: 10.3389/fnins.2018.00250
|View full text |Cite
|
Sign up to set email alerts
|

The Scalp Time-Varying Networks of N170: Reference, Latency, and Information Flow

Abstract: Using the scalp time-varying network method, the present study is the first to investigate the temporal influence of the reference on N170, a negative event-related potential component (ERP) appeared about 170 ms that is elicited by facial recognition, in the network levels. Two kinds of scalp electroencephalogram (EEG) references, namely, AR (average of all recording channels) and reference electrode standardization technique (REST), were comparatively investigated via the time-varying processing of N170. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…10). This phenomenon is further confirmed by a simulation study in (Tian et al 2017). This means that reference is an important issue in precise investigation of the spatial–temporal dynamics of ERP, and REST based zero-reference would be the first step for the following explanation of various ERPs.
Fig.
…”
Section: Impact Of the Unipolar Reference On Real Data Analysissupporting
confidence: 71%
See 1 more Smart Citation
“…10). This phenomenon is further confirmed by a simulation study in (Tian et al 2017). This means that reference is an important issue in precise investigation of the spatial–temporal dynamics of ERP, and REST based zero-reference would be the first step for the following explanation of various ERPs.
Fig.
…”
Section: Impact Of the Unipolar Reference On Real Data Analysissupporting
confidence: 71%
“…10Recorded data derives the time-varying networks of N170. Hubs and connection mode change over time near 170 ms under the three different significance levels.(Reproduced with permission from Tian et al 2017)…”
Section: Impact Of the Unipolar Reference On Real Data Analysismentioning
confidence: 99%
“…For example, compared with the mastoid reference, common average reference reinforced the emotional modulation effects at the occipitotemporal electrodes where the N170 ERPs typically occurred (Rellecke et al, 2013 ; Hinojosa et al, 2015 ). Moreover, our recent study also revealed that the reference technique might play a crucial role in ERPs data interpretation, and we found that REST reference would be a superior choice for precise evaluation of the scalp spatiotemporal changes connected to various cognitive events (Tian et al, 2018 ). In the current study, we found that N170 could be modulated by emotion when ERPs were re-referenced by REST (Yao, 2001 ; Tian and Yao, 2013 ), which supported the opinions that the processing of facial recognition and expression were integrated mechanisms rather than segregated mechanisms (Hinojosa et al, 2015 ; Song et al, 2017 ), and that the effects of emotional modulation on facial recognition might be associated with the reference technique (Rellecke et al, 2013 ; Hinojosa et al, 2015 ).…”
Section: Discussionmentioning
confidence: 88%
“…WMNE was performed on scalp maps of selected ICA components to find the maximal densities of their cortical sources 41,42 . For valid ICA components, the source location was estimated by Eq.…”
Section: Methodsmentioning
confidence: 99%